The Neurospora crassa PCL-1 cyclin is a PHO85-1 (PGOV) kinase partner that directs the complex to glycogen metabolism and is involved in calcium metabolism regulation - Campanella, Jonatas Erick Maimoni; Candido, Thiago de Souza; Barbosa, Luiz Carlos Bertucci; Gomes, Antoniel Augusto Severo; Leite, Carla Andréa; Higashi, Erika Silva; Barbugli, Paula Aboud; Fontes, Marcos Roberto de Matos; Bertolini, Maria Célia (Frontiers in Microbiology, 2022)
Cyclins are a family of proteins characterized by possessing a cyclin box domain that mediates binding to cyclin dependent kinases (CDKs) partners. In this study, the search for a partner cyclin of the PHO85-1 CDK retrieved PCL-1 an ortholog of yeast Pcls (for Pho85 cyclins) that performs functions common to Pcls belonging to different cyclin families. We show here, that PCL-1, as a typical cyclin, is involved in cell cycle control and cell progression. In addition, PCL-1 regulates glycogen metabolism; ∆pcl-1 cells accumulate higher glycogen levels than wild-type cells and the glycogen synthase (GSN) enzyme is less phosphorylated and, therefore, more active in the mutant cells. Together with PHO85-1, PCL-1 phosphorylates in vitro GSN at the Ser636 amino acid residue. Modeling studies identified PHO85-1 and PCL-1 as a CDK/cyclin complex, with a conserved intermolecular region stabilized by hydrophobic and polar interactions. PCL-1 is also involved in calcium and NaCl stress response. ∆pcl-1 cells are sensitive to high NaCl concentration; on the contrary, they grow better and overexpress calcium responsive genes under high calcium chloride concentration compared to the wild-type strain. The expression of the calcium-responsive CRZ-1 transcription factor is modulated by PCL-1, and this transcription factor seems to be less phosphorylated in ∆pcl-1 cells since exhibits nuclear location in these cells in the absence of calcium. Our results show that PCL-1 locates at different cell regions suggesting that it may determine its activity by controlling its intracellular location and reveal an interesting functional divergence between yeast and filamentous fungus cyclins.